Gerakan Desa Sehat Tanpa Rokok: Edukasi Bahaya Merokok Bagi Masyarakat - Musaidah Musaidah; Rahmat Pannyiwi; Serly Sani Mahoklory; Ferdic Sukma Wahyudin (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Smoking remains a serious health problem in rural communities. High cigarette consumption increases the risk of non-communicable diseases, respiratory disorders, and places a financial burden on families. This community service activity aims to increase community knowledge and awareness of the dangers of smoking through the "Healthy Village Movement Without Smoking" program. Methods used include health education, group discussions, visual demonstrations, the formation of anti-smoking cadres, and the declaration of smoke-free areas within the village. The results of this activity indicate increased community knowledge, changes in attitudes toward the dangers of smoking, and a shared commitment to reducing smoking. This program is expected to develop into an independent and sustainable healthy village movement.